Nonlinear optical properties of peripheral symmetrically and non-symmetrically 4-(trifluoromethoxy)phenoxy substituted zinc phthalocyanines - GÖRK, GÜLŞEN; ERDEM, MURAT (ELSEVIER SCIENCE SA, 2020)
In this work, new non-symmetrical, peripherally substituted metallophthalocyanines, namely 2(3)-[(4-nitrophenyeethynyl]-{9,10,16,17, 23, 24-hexakis-(4-(trifluoromethoxy)phenoxy)-phthalo cyaninato zinc (1 b) and 2(3)-[(4-nitrophenyeethynyl]-{9(10),16(17),23(24)-tris-(4-(trifluoromethoxy)phenoxy)-phthalocyaninatolzinc (2b) were prepared. Structural elucidation of the novel zinc phthalocyanines was carried out with well-known spectroscopic methods. The solubility of the phthalocyanines was investigated in organic solvents like tetra-hydrofuran, dichloromethane, and dimethyl sulfoxide. The effect of concentration on aggregation behavior of the resulting phthalocyanines (1b and 2b) was examined in a wide area ranging from 4 x 10(-6) to 14 x 10(-6) M in tetrahydrofuran. Aggregation properties of the macrocyclic molecules (1b and 2b) were also investigated in many organic solvents. Based on the data existing in the literature, peripherally octa- and tetra-substituted zinc phthalocyanines (1a and 2a) with 4-(trifluoromethoxy)phenoxy moieties were synthesized. Optical limiting and the third-order nonlinear properties of symmetrically and non-symmetrically substituted phthalocyanines were determined and compared with each other.
Keywords: Fluorinated phthalocyanines; NLO properties; Optical limiting; Symmetric and non-symmetric phthalocyanine; 4-(Trifluoromethoxy)phenoxy; UNSYMMETRICAL PHTHALOCYANINE; DERIVATIVES; BEHAVIOR; TARGETS